Transformative Learning through Action Research: A Case Study from South Africa - Sarah Gravett (Adult Education Research Conference, 2002)
The paper reports on the results of an action research project, informed by transformative theory. The action research was designed to change faculty perspectives and practices from a teacher-centered to a learning-centered dialogic approach, underpinned by a socio-constructivist epistemology.